2017
DOI: 10.1111/josi.12251
|View full text |Cite
|
Sign up to set email alerts
|

The Trauma Lens of Police Violence against Racial and Ethnic Minorities

Abstract: Police violence against racial and ethnic minorities has been researched through the lens of multiple social science disciplines including psychology. Within psychology, the study of trauma lends itself to understanding the dynamics of unjustified violence perpetrated by some law enforcement agents. These acts of aggression are not only examples of interpersonal trauma but also the trauma of racism, which is examined through the lens of intergenerational trauma, racistincident-based trauma, and complex trauma.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
113
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(130 citation statements)
references
References 67 publications
(74 reference statements)
3
113
0
4
Order By: Relevance
“…In this special issue, Reinka and Leach () found that Black participants had stronger reactions to police violence than White participants, despite greater familiarity with the experience. This may also be viewed through the paradigm of police violence as racial trauma outlined by Bryant‐Davis and colleagues (). Future research can examine why knowledge of police bias does not impact overall perceptions for certain racial groups, genders, or people with other identities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this special issue, Reinka and Leach () found that Black participants had stronger reactions to police violence than White participants, despite greater familiarity with the experience. This may also be viewed through the paradigm of police violence as racial trauma outlined by Bryant‐Davis and colleagues (). Future research can examine why knowledge of police bias does not impact overall perceptions for certain racial groups, genders, or people with other identities.…”
Section: Discussionmentioning
confidence: 99%
“…When people of color have more frequent negative contacts with police and are targeted via racial profiling methods, their mistrust and negative opinions of law enforcement increases (Cochran & Warren, ). Recent research included in this Special Issue has also suggested that repeated negative contacts with police, whether experienced directly or vicariously through social media, news coverage, or intergenerational transmission of narratives and beliefs, can be viewed as a form of racial trauma, which may alter people of color's perceptions of safety and their views on the police (Bryant‐Davis, Adams, Alejandre, & Gray, ).…”
mentioning
confidence: 99%
“…Continuing on this theme, Bryant‐Davis, Adams, Alejandre, and Gray () provide a critical review of literature on police brutality and disparate treatment (e.g., stop‐and‐frisk searches, identification checks) of racial and ethnic minorities in the United States and beyond through multiple trauma frameworks, namely, complex trauma and intergenerational trauma. Complex trauma is characterized as a subset of dangerous or harmful events in which the person suffers traumatic shock, and also severe disruption in the development of core self‐regulatory competences (Ford, ).…”
Section: Overview Of Current Issuementioning
confidence: 99%
“…Bryant‐Davis et al. () conclude by outlining novel ways in which these frameworks can inform medical, judicial, and clinical policies and procedures.…”
Section: Overview Of Current Issuementioning
confidence: 99%
“…In contrast to most other articles in this issue, we do not directly study antecedents and consequences of blatant aggressive behaviors by the police (e.g., Bryant‐Davis, Adams, Alejandre, & Gray, ; Charbonneau, Spencer, & Glaser, ; Kahn & Davies, ; Scott, Ma, Sadler, & Correll, ). This is due to the fact that our research was conducted among immigrant minority members in three European countries (i.e., Germany, the Netherlands, and Sweden) .…”
mentioning
confidence: 98%